Assessment of Carbon Credit Opportunities and Industrial Wastewater Treatment: A Process Engineering Perspective - Nurlilasari, Puspita; Saallah, Saryani; Lenggoro, Wuled (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2026)
Industrial wastewater treatment is increasingly recognized as a strategic sector for climate change mitigation. Integrating carbon credit mechanisms with process engineering solutions offers opportunities to convert pollution control infrastructure into measurable greenhouse gas (GHG) reduction assets by linking greenhouse gas recovery, energy utilization, and environmental compliance. Aim: This study aims to identify emission reduction potential and evaluate how financial incentives from carbon credit markets can enhance the feasibility of wastewater treatment investments for industries, municipalities, and Non-Governmental Organizations (NGOs). Methodology and results: using Clean Development Mechanism (CDM) and mixed-method approach, this study indicates promising results that anaerobic technologies such as Upflow Anaerobic Sludge Blanket reactors and covered lagoons can remove 70–90% of Chemical Oxygen Demand (COD) while producing recoverable greenhouse gas equivalent to significant Carbon dioxide emissions reductions annually. Compared with conventional aerobic treatment, inclusion of carbon revenue improves project attractiveness, with estimated payback periods between 3 and 7 years. Conclusion, significance and impact study: carbon credit opportunities in wastewater treatment are primary driven by techno-economic ability of process technologies to recover greenhouse gas, reduce emissions, and create economic value. the assessment shows that anaerobic systems provide both environmental improvement and financial returns, making industries more willing to adopt cleaner treatment solutions. The availability of carbon revenue increases the attractiveness of investment and accelerates modernization of existing facilities. Wastewater treatment industry is no longer viewed solely as pollution control units, but as platforms for energy recovery and climate mitigation. The implementation of carbon-oriented wastewater management supports urban environmental protection while strengthening industrial competitiveness. The approach contributes directly on achieving SDG 6.